The Emerging Roles of Long Noncoding RNAs as Hallmarks of Lung Cancer - Jiang, Jun; Lu, Yuan; Zhang, Fang; Huang, Jie; Ren, Xin-ling; Zhang, Rui (Frontiers in Oncology, 2021)
Noncoding ribonucleic acids (ncRNAs) are closely associated with tumor initiation, growth, and progress in lung cancer. Long ncRNAs (lncRNAs), as one of the three subclasses of ncRNAs, play important roles in chromatin modification, transcription, and post-transcriptional processing. Various lncRNAs have recently been reported to be dysfunctional or dysregulated in cancers and have pro- or anti-tumor potential. Importantly, as a new class of cancer biomarkers, studies have demonstrated the plausibility of using certain subsets of lncRNAs as promising diagnostic, therapeutic, or prognostic strategies to manage cancers. This review focuses on lncRNAs associated with hallmarks of lung cancer, especially those discovered in the last five years. The expression levels of these lncRNAs in tumor samples are discussed, alongside their mechanisms of action, drug resistance, and potential as diagnostic and prognostic markers for lung cancer.